Factors Associated with Quality of Life in People with Lower Limb Amputations - Farahani Nia M; Maleki M; Khayeri F; Haghani H (Iran University of Medical Sciences, 2012)
Background & Aims: Amputation of a body part is a "life-changing event" . Amputation affects almost all aspects of an individual's life. Many issues arise following the loss of all or part of a person's limb(s) . Disability as a consequence of amputation has a devastating effect on the quality of life of the disabled people . The aim of this study was to investigate the factors associated with quality of life in people with lower limb amputations   Material & Methods: It was a descriptive, cross-sectional study . The study population consisited of all above 18 years refferd to the rehabilitation center of Tehran during 2008 who had lost part or all of their lower limb due to disease or accident.Data was collected by the Short Form 36 Item Health Survey Questionner (SF36),and a researcher made tool ,and analyzed using SPSS-PC(v.12).   Results: The score of the quality of life of most study sample (%59/2) was 34-46. The mean and standard deviation of total quality of life was 55.02±17.226. there were a significant relationship between the quality of life and the samol's age, marital status, number of children, education, job status ( before and after amputation), financial status, residence, the status of residence, type of insurance, type of home, the amputated limb, the level of amputation, the time after amputation, using prosthesis, use of assistive devices, and the reson for amputation (P > 0/05).   The regression analysis revealed that the factors associated with quality of life in order of importance were using prosthesis, financial status, the reson for amputation, and the number of children.   Conclusions: Identification of these factors for consultation, planning and implementing appropriatemhealth policies to improve quality of life of these individuals is recommended.